Differential Contribution of NF-κB Signaling Pathways to CD4+ Memory T Cell Induced Activation of Endothelial Cells - Jeucken, Kim C. M.; van Rooijen, Charlotte C. N.; Kan, Yik Y.; Kocken, Lotte A.; Jongejan, Aldo; van Steen, Abraham C. I.; van Buul, Jaap D.; Olsson, Henric K.; van Hamburg, Jan Piet; Tas, Sander W. (Frontiers in Immunology, 2022)
Endothelial cells (ECs) are important contributors to inflammation in immune-mediated inflammatory diseases (IMIDs). In this study, we examined whether CD4+ memory T (Tm) cells can drive EC inflammatory responses. Human Tm cells produced ligands that induced inflammatory responses in human umbilical cord EC as exemplified by increased expression of inflammatory mediators including chemokines and adhesion molecules. NF-κB, a key regulator of EC activation, was induced by Tm cell ligands. We dissected the relative contribution of canonical and non-canonical NF-κB signaling to Tm induced EC responses using pharmacological small molecule inhibitors of IKKβ (iIKKβ) or NF-κB inducing kinase (iNIK). RNA sequencing revealed substantial overlap in IKKβ and NIK regulated genes (n=549) that were involved in inflammatory and immune responses, including cytokines (IL-1β, IL-6, GM-CSF) and chemokines (CXCL5, CXCL1). NIK regulated genes were more restricted, as 332 genes were uniquely affected by iNIK versus 749 genes by iIKKβ, the latter including genes involved in metabolism, proliferation and leukocyte adhesion (VCAM-1, ICAM-1). The functional importance of NIK and IKKβ in EC activation was confirmed by transendothelial migration assays with neutrophils, demonstrating stronger inhibitory effects of iIKKβ compared to iNIK. Importantly, iIKKβ – and to some extent iNIK - potentiated the effects of currently employed therapies for IMIDs, like JAK inhibitors and anti-IL-17 antibodies, on EC inflammatory responses. These data demonstrate that inhibition of NF-κB signaling results in modulation of Tm cell-induced EC responses and highlight the potential of small molecule NF-κB inhibitors as a novel treatment strategy to target EC inflammatory responses in IMIDs.